Proposal of a method for routing school buses in a small-sized county - Muzulon, Nádya Zanin (2022)
The School Bus Routing Problem (SBRP) is widely discussed in the operations research literature and can be solved by several exact methods and heuristics. This problem seeks to designate the most efficient routes for a fleet of school buses, minimizing the total distance covered and considering variables such as bus stop locations, number of passengers, and the assigned destination for each of them. This study aims at solving a real case SBRP of a small-sized county located in the state of Paraná. The proposed method is based on the Capacitated Vehicle Routing Problem (CVRP) and Travelling Salesman Problem (TSP) combined with a heuristic correction that guarantees sequence constraints, in which the student has to be collected before visiting their destination school. It was possible to obtain two routes of 30.76 km and 17.42 km respectively and both with the total vehicles’ capacity of 24 students, which corresponds to the reduction of about 10% in the daily distance covered by two buses.